Relações com o saber : um estudo sobre o sentido atribuído por alunos da rede pública à escola, à língua inglesa e à sua aprendizagem - Ianuskiewtz, Andréia Dias (Universidade Federal de São Carlos, 2014)
In this qualitative study, we aim to investigate the senses of learning English and the relationships established by elementary school students in the context of public school education with the world (with the transmitted/acquired knowledge in school, with the school, the classroom and everything that surrounds it), with the other (teachers and peers) and with themselves (their knowledge, their expectations, their goals and motives). Thus, the research focuses on understanding the meaning that the school has for students and the conceptions they have about the English language and its learning, considering the epistemic, personal and social dimensions of knowledge. It also seeks to identify the processes that structure the motivation to learn English and the mobilization to learn the language. The work is based on studies conducted by Bernard Charlot (2000, 2001, 2005) about the relationship to knowledge, which seek to understand how the subject categorizes and organizes their world, how they attribute meaning to their experience, especially their school experience. The theoretical basis of this research is also composed by principles and concepts that constitute the Activity Theory, developed by Vigotski (1980, 2001, 2005, 2007) and Leontiev (1978, 1984), as well as conceptions about motivation, within the area of language teaching and learning (DÖRNYEI, 2001; DÖRNYEI & USHIODA, 2013; GARDNER, 2002, 2010; DECI & RYAN, 2000; VIANA, 1990). Data collection involved classroom observations in two 6th grade classes of elementary school of two public schools in the state of São Paulo during the period of one year, and it included the following instruments: questionnaires, drawings produced by the students, researcher's field diaries and interviews. Through data analysis, we found that students recognize the role of the school as a learning space, but the relationship they establish with the institution is based on the valuing of relational/affective learnings. We observed that students begin the 6th grade with a positive perception of the English language and they are motivated to learn it, but in spite of this, there is neither mobilization nor establishment of personal sense, due to the mismatch between motives and purposes of the learning activities.
Keywords: Relação com o saber; Teoria da atividade; Língua inglesa; Escolas públicas; Relationship to knowledge theory; Activity theory; Motivation; Personal sense; English learning; Public school; LINGUISTICA, LETRAS E ARTES::LINGUISTICA